2022
DOI: 10.3389/fenrg.2022.980042
|View full text |Cite|
|
Sign up to set email alerts
|

Energy and mass transport through hybrid nanofluid flow passing over an extended cylinder with the magnetic dipole using a computational approach

Abstract: The objective of this research is to evaluate the heat and mass transfer in a water-based Darcy–Forchheimer hybrid nanofluid (HNF) flow across an expanding cylinder. The fluid flow has been studied under the influence of a magnetic field, viscous dissipation, heat source, thermal radiation, concentration stratification, and chemical reaction. Carbon nanotubes (CNTs) and iron ferrite (Fe3O4) nanoparticles (NPs) are added to the water, for the purpose of synthesizing the HNF. The fluid flow has been induced in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In (Taylor, 1923), it was found that the special type of instability is prominent for fluid flow over concave and convex sheets, subject to the condition that the velocity components are non-monotonic in nature. In (Ghalambaz et al, 2016;Hayat et al, 2017;Srinivasacharya and Sibanda, 2020;Mahmud and Uddin, 2021), numerical simulation and analysis of different types of nanofluids flowing past various types of surfaces in the context of fluid flow and heat transfer in different channels was performed (Khan and Ahmed, 2015;Alsaedi et al, 2016;Nadeem et al, 2016;Izadi and Pourmehran, 2017;Khan et al, 2017;Sheikholeslami et al, 2017). These studies explore the impact of various factors such as thermal radiation, magnetic fields, bioconvection, entropy optimization, and chemical reactions on flow and heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In (Taylor, 1923), it was found that the special type of instability is prominent for fluid flow over concave and convex sheets, subject to the condition that the velocity components are non-monotonic in nature. In (Ghalambaz et al, 2016;Hayat et al, 2017;Srinivasacharya and Sibanda, 2020;Mahmud and Uddin, 2021), numerical simulation and analysis of different types of nanofluids flowing past various types of surfaces in the context of fluid flow and heat transfer in different channels was performed (Khan and Ahmed, 2015;Alsaedi et al, 2016;Nadeem et al, 2016;Izadi and Pourmehran, 2017;Khan et al, 2017;Sheikholeslami et al, 2017). These studies explore the impact of various factors such as thermal radiation, magnetic fields, bioconvection, entropy optimization, and chemical reactions on flow and heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of radiative stagnation point fow of nanofuid with cross-difusion and viscous dissipation, Qaiser et al [23] illustrated the relevance of entropy optimization and activation energy. Using a computational technique, Khan et al [24] explored the movement of mass and energy in a hybrid nanofuid fowing across an extended cylinder containing a magnetic dipole. Nonlinear radiative nanofuidic hydrothermal unsteady bidirectional transport with thermal/mass convection issues was researched by Faisal et al [25].…”
Section: Introductionmentioning
confidence: 99%